Spectris™ treatment preserves corpus callosum structure in Alzheimer's disease - Da, Xiao; Hempel, Evan; Brickman, Adam M.; Hajós, Mihály; Kern, Ralph; Cimenser, Aylin (Frontiers in Neurology, 2024)
Objective To examine the impact of 40Hz gamma stimulation on the preservation of the corpus callosum, a critical structure for interhemispheric connectivity, in people with mild cognitive impairment or Alzheimer's disease. Methods OVERTURE (NCT03556280) participants were randomized 2:1 (Active:Sham) to receive daily, 1-h, 40Hz gamma sensory stimulation or sham treatment for 6 months. Structural magnetic resonance imaging data were analyzed to assess changes in corpus callosum area (N = 50; 33 for active, 17 for sham). Bayesian linear mixed-effects modeling was used to assess differences in longitudinal changes of corpus callosum area between the two treatment groups. Results All observed differences in corpus callosum area favored the active treatment group. Differences were observed in the total corpus callosum area (2.28 ± 0.87%, p < 0.02) and its subregions, including genu/rostrum (2.36 ± 0.90%, p < 0.02), anterior-body (2.64 ± 1.26%, p < 0.04), mid-body (2.79 ± 1.18%, p < 0.03), posterior-body (2.87 ± 1.41%, p < 0.05), and splenium (1.58 ± 0.73%, p < 0.04). Total corpus callosum area and some of the sub-regional differences, such as genu/rostrum and splenium, were observed as early as 3 months after commencement of treatment. Interpretation The structural magnetic resonance imaging results from the OVERTURE Phase 2 study suggest that 6 months of non-invasive 40Hz stimulation reduces the rate of atrophy of the corpus callosum in individuals with Alzheimer's disease. The preservation of structural integrity in the corpus callosum, crucial for interhemispheric communication and cognitive function, may be achievable through this non-invasive approach, potentially providing a promising disease-modifying alternative in Alzheimer's disease management.